David's Wives: Love, Power, and Lust - Zucker, David J. (Biblical theology bulletin, 2016)
David's rise to the monarchy and the early consolidation of his dynasty connect directly to several of his wives, most notably Michal, Abigail, and Bathsheba. These women were not his only wives; however, they were pivotal figures in establishing and maintaining his place on the throne, and certainly the particular direction of his dynasty. David's relationships – at least initially –with these three women are characterized respectively by the words love, power, and lust.